ANALYSIS OF CUSTOMER INTEREST USING SOE BANK MOBILE BANKING WITH TECHNOLOGY ACCEPTANCE MODELS - Ibnu Haris Nasution; Rahmat, Rahmat (Sean Institute, 2023)
The development of banking services is no longer only with the slogan of safe and reliable services, but also being able to provide services tailored to the needs of customers who have developed in line with developments in technology and lifestyle. One form of service developed by banks is online banking services. Online banking is a banking transaction service that can be carried out by customers either from home, place of business or in other locations that are not in a real bank location (branch offices) by using communication media such as computers, cell phones and home phones. Sampling by technique sampling that is accidental sampling based on the formula Sampling proportion . For collection data includes observation, distribution of questionnaires and literature study. The purpose of this study was to determine the interest in using the Mobile Banking services of BUMN Banks with the Technology Acceptance Model. Approach study Which used in this study is a quantitative approach with a total sample of 100 respondents with the results of the analysis showing that the variable Perceived Usefulness has a significant effect on Attitude, Partial Least Square (PLS) analysis shows that Perceived Ease of Use variable has a significant effect on Attitude, Partial Least Square (PLS) analysis shows that Perceived Usefulness variable has a significant effect on Interest in using mobile banking